The Concentration / Conduct Relationship in Bank Deposit Markets - Calem, Paul S.; Carlino, Gerald A. (The Review of Economics and Statistics, 1991)
This study investigates the structure/conduct/performance relationship in retail deposit markets. The study explicitly incorporates conduct as the link between structure and performance in local deposit markets. It attempts to determine whether banks typically behave competitively or strategically, and whether their conduct is influenced by market concentration. The empirical investigation is guided by an equilibrium model of a retail deposit market. The model is applied to regression equations for local (MSA) MMDA and three- and six-month CD rates. The empirical results indicate that strategic conduct is the norm in MMDA and in three- and six-month CD markets. Copyright 1991 by MIT Press.